Clinical and Morphological Aspects of Male Germ Cells - Samikhovna, Mukhitdinova Khurshida (American Journal of Bioscience and Clinical Integrity, 2024)
The sperm is the male germ cell, which plays an important role in sexual reproduction. Without this cell, the process of fertilization and combinative variability is impossible, therefore, it is necessary to know the features of the stages of maturation of the sperm, the variants of the pathological structure of the cells of the spermatogenic series, its life cycle both in the body of a man and in the body of a woman.